Workplace spirituality in Indian organisations: construction of reliable and valid measurement scale - Pradhan, Rabindra Kumar; Jenar, Lalatendu Kesari; Soto, Cesar Merino (Business: Theory and Practice, 2017)
The purpose of the paper was to develop and validate a comprehensive tool for measuring workplace spirituality. On the basis of literature, feedback from academic and industry professionals, a heuristic framework along with a scale on workplace spirituality was proposed and a questionnaire was developed. The instrument obtained empirical views from experts on its dimensions and statements. Content validity ratio (CVR) of the instrument was carried out and the retained items were taken for field survey. Three hundred and sixty one executive respondents employed in manufacturing and service organisations in Indian subcontinent responded to the 44 items scale assessing different facets of spirituality at workplace. This helped to validate the factors of workplace spirituality and optimize the contents of the proposed instrument with the help of structural equation modelling. Exploratory factor analysis revealed four distinct factors that constitute the new instrument of workplace spirituality: spiritual orientation, compassion, meaningful work, and alignment of values. Reliability analysis reported high level of internal consistency of the total scale (α = .78) and the five subscales (α’s ranging from .75 to .87). Finally, 30 items were retained with four important factors of Workplace Spirituality Scale.